Intraoperative Generalized Tonic-Clonic Seizure and Consequent Severe Brain Bulge During Functional Motor Cortex Mapping: A Case Report. Issue 3 (1st February 2019) - Khandelwal, Ankur; Singh, Gyaninder Pal; Singh, Akanksha; Singh, Shalendra; Prasad, Chandrakant
Abstract : Intraoperative cortical and subcortical bipolar or monopolar mapping is the gold standard for neurosurgical procedures that involve lesions near functional or "eloquent" cortex. However, the classic Penfield stimulation has a higher intraoperative seizure rate than high-frequency short-train stimulation. As a result, high-frequency monopolar stimulation is now the most widely practiced technique. However, seizure-free mapping cannot be guaranteed even with high-frequency stimulation particularly at high current thresholds. We encountered a case of severe generalized tonic-clonic seizure and consequent severe brain bulge in an 8-year-old child during cortical mapping with the high-frequency protocol.